The effects of circadian desynchronization on alcohol consumption and affective behavior during alcohol abstinence in female rats - Meyer, Christiane; Schoettner, Konrad; Amir, Shimon (Frontiers in Behavioral Neuroscience, 2022)
Disruption of circadian rhythmicity distorts physiological and psychological processes and has major consequences on health and well-being. A chronic misalignment within the internal time-keeping system modulates alcohol consumption and contributes to stress-related psychiatric disorders, which are known to trigger alcohol misuse and relapse. While there is growing evidence of the deleterious impact of circadian disruption on male physiology and behavior, knowledge about the effect in females remains limited. The present study aims to fill the gap by assessing the relationship between internal desynchronization and alcohol intake behavior in female rats. Female Wistar rats kept under standard 24-h, 22-h light-dark conditions, or chronic 6-h advanced phase shifts, were given intermittent access to 20% alcohol followed by an extended alcohol deprivation period. Alcohol consumption under altered light-dark (LD) conditions was assessed, and emotional behavior during alcohol abstinence was evaluated. Internally desynchronization in female rats does not affect alcohol consumption, but alters scores of emotionality during alcohol abstinence. Changes in affective-like behaviors were accompanied by reduced body weight gain and estrous irregularities under aberrant LD conditions. Our data suggest that internal desynchronization caused by environmental factors is not a major factor contributing to the onset and progression of alcohol abuse, but highlights the need of maintaining circadian hygiene as a supportive remedy during alcohol rehabilitation.